2020
DOI: 10.1371/journal.pone.0233512
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the longitudinal association between obesity, and disability with workplace absenteeism in the Australian working population

Abstract: Background Excess weight can increase absenteeism of workers and can have a negative influence on their productivity. Current evidence on this association is mostly based on cross-sectional data and there is little evidence concerning the longitudinal relationship between obesity, and disability with workplace absenteeism. Further, gender differences in this association have often ignored in the existing literature. Objectives This study aims to examine gender differences in the longitudinal association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…The primary outcome of this study is self-reported disability status. The survey collected data on respondents' disability status following the International Classification of Functioning, Disability, and Health (ICF) guidelines under the WHO framework ( Keramat et al, 2020a , 2020b , 2020c ; LaMontagne et al, 2016 ; Lopez Silva et al, 2020 ). The term ‘disability’ has been used as umbrella term covering impairments, functional limitations, and participation restriction in the definition of ICF ( World Health Organization, 2001 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcome of this study is self-reported disability status. The survey collected data on respondents' disability status following the International Classification of Functioning, Disability, and Health (ICF) guidelines under the WHO framework ( Keramat et al, 2020a , 2020b , 2020c ; LaMontagne et al, 2016 ; Lopez Silva et al, 2020 ). The term ‘disability’ has been used as umbrella term covering impairments, functional limitations, and participation restriction in the definition of ICF ( World Health Organization, 2001 ).…”
Section: Methodsmentioning
confidence: 99%
“…Further, disabled people are less likely to be in the workforce and have substantially less personal income compared with adults without disability ( Australian Bureau of Statistics, 2018 ). Additionally, there is evidence that disabled people have lower productivity in the workplace in the form of lower levels of job satisfaction ( Keramat, Alam, Gow, & Biddle, 2020a , 2020b , 2020c , 2020d ), higher absenteeism ( Keramat et al, 2020a , 2020b , 2020c , 2020d ) and presenteeism ( Keramat et al, 2020a , 2020b , 2020c , 2020d ) compared with non-disabled counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…1 The HILDA survey collects information on the disability status of the participants in every wave through personal interviews following the International Classification of Functioning, Disability and Health (ICF) under the WHO framework guidelines. 9,[23][24][25][26] Disability status was assessed using the question, Do you have any long-term health conditions, impairment or disability that restricts your everyday activities, and has lasted or are likely to last for six months or more?…”
Section: Exposure Variablesmentioning
confidence: 99%
“…Overweight and obesity are linked with an increased risk of non-communicable diseases (NCDs), such as cancers, cardiovascular diseases, musculoskeletal disorders, kidney disease, diabetes, asthma, dementia, sleep apnea 1 , 6 , 7 , and long-term health conditions or disability 8 . Further, obesity contributes substantially to labour productivity losses in the form of high absenteeism 9 , presenteeism 10 and low job satisfaction 11 in the workplace. Therefore, the future direct (health burden) and indirect (productivity loss) costs will more likely increase with obesity’s rising prevalence in Australian society.…”
Section: Introductionmentioning
confidence: 99%